2015
DOI: 10.1152/japplphysiol.00114.2015
|View full text |Cite
|
Sign up to set email alerts
|

Depth-dependent variations in Achilles tendon deformations with age are associated with reduced plantarflexor performance during walking

Abstract: The anatomical arrangement of the Achilles tendon (AT), with distinct fascicle bundles arising from the gastrocnemius and soleus muscles, may facilitate relatively independent behavior of the triceps surae muscles. A reduced capacity for sliding between adjacent tendon fascicles with age may couple gastrocnemius and soleus muscle behavior, thereby potentially contributing to diminished plantarflexor performance commonly observed in old adults. Nine healthy young (mean age, 23.9 yr) and eight healthy old (69.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 37 publications
6
42
0
Order By: Relevance
“…The influence of this design on muscle fascicle and tendon energetics remains an area of future research. We note here, however, that recent in vivo studies on non-uniform Achilles tendon deformation have observed that tendon fascicles arising from the SO and gastrocnemius may function as independent structures during walking [67,68].…”
mentioning
confidence: 52%
“…The influence of this design on muscle fascicle and tendon energetics remains an area of future research. We note here, however, that recent in vivo studies on non-uniform Achilles tendon deformation have observed that tendon fascicles arising from the SO and gastrocnemius may function as independent structures during walking [67,68].…”
mentioning
confidence: 52%
“…Muscle-tendon unit (MTU) lengths for both MG and soleus were calculated from the joint kinematics using regression equations defined by Hawkins & Hull (16). Tendinous tissue (TT, including both proximal and distal free tendon and aponeurosis) lengths for both MG and soleus were calculated as L TT = L MTU -L FAS* cos(pennation angle), where L MTU is MTU length and L FAS is muscle fascicle length (15). MTU and TT lengths were normalized by dividing them by their corresponding reference lengths, which were determined in the same way as the muscle fascicle reference lengths.…”
Section: Muscle-tendon Unit and Tendon Lengthmentioning
confidence: 99%
“…In fact, we showed earlier that 6-minute walking test results positively correlate with Achilles tendon stiffness in older adults (39). Additionally, recent studies using ultrasound imaging and musculoskeletal modeling have started to unfold more complex interactions between Achilles tendon mechanical properties and triceps surae muscle function in which age-related Achilles tendon interfascicular adhesions coupling gastrocnemius and soleus muscle function may contribute to the reduced plantarflexor performance in walking in older adults (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, we have adopted a novel 2D ultrasound speckle-tracking algorithm to directly image localized Achilles tendon tissue motion in vivo . We have previously elaborated on the technical details of the approach, its validity, and its use during functional and dynamic activities (Chernak et al 2012, Slane et al 2014, Franz et al 2015). In our ongoing experimental work, we use this technique to characterize differences in tendon tissue deformations (i.e., displacements and elongations) during walking between regions of the Achilles free tendon thought to arise from the gastrocnemius and soleus muscles (Franz et al 2015) and how this in vivo behavior changes with aging (Franz et al 2015).…”
Section: Characterizing In Vivo Achilles Tendon Tissue Deformationsmentioning
confidence: 99%
“…Our recent contributions to these efforts have focused on the in vivo characterization of localized AT deformations during walking and the relevance of those deformations to degradations in triceps surae mechanical performance due to aging (Franz et al 2015, Franz et al 2015). Compared to younger tendons, older tendons are thought to exhibit a reduced capacity for inter-fascicle sliding potentially arising from a proliferation of collagen cross-linking and inter-fascicle adhesions (Thorpe et al 2013).…”
Section: Introductionmentioning
confidence: 99%